(untitled) (Sociologisk Forskning, 2002)
Forms of interaction In this article, the theoretical notion of forms of interaction is introduced, which comprehends how the network and domain structures provide a background for interaction. This general approach is used to discuss how persons can style their identities. Today’s forms of interaction enable people to hide information in interaction with other people. People can, for example, present themselves as individualized, important and successful in interaction with others. This facilitates the emergence of certain values. Especially individualistic values are studied in this article.